Endodontic Irrigation 2015
DOI: 10.1007/978-3-319-16456-4_18
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation in Regenerative Endodontic Procedures

Abstract: The developing dentition is at risk for pulpal necrosis due to trauma and developmental dental anomalies such as dens evaginatus. Loss of an immature permanent tooth in young patients with mixed dentition can be devastating, leading to loss of function, malocclusion, and inadequate maxillofacial development. These teeth traditionally have been treated with apexifi cation procedures using either long-term calcium hydroxide treatment or immediate placement of a mineral trioxide aggregate (MTA) apical plug. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
1
0
0
2
Order By: Relevance
“…The difference in cell viability between the Ca(OH) 2 and TAP groups may be due to the high pH (12.5–12.8) of Ca(OH) 2 , which can lead to immediate cell apoptotic upon contact, so it can be concluded that TAP was less toxic to Ca(OH) 2 . 7 27 28 This aligns with the research conducted by Jamshidi et al, where TAP concentrations of 0.1 and 1 mg/mL provided good viability in SCAP and will be toxic with higher concentrations. 18…”
Section: Discussionsupporting
confidence: 88%
“…The difference in cell viability between the Ca(OH) 2 and TAP groups may be due to the high pH (12.5–12.8) of Ca(OH) 2 , which can lead to immediate cell apoptotic upon contact, so it can be concluded that TAP was less toxic to Ca(OH) 2 . 7 27 28 This aligns with the research conducted by Jamshidi et al, where TAP concentrations of 0.1 and 1 mg/mL provided good viability in SCAP and will be toxic with higher concentrations. 18…”
Section: Discussionsupporting
confidence: 88%
“…uzavřený apex s normální šířkou periodontální štěrbiny. Tento stav je vzhledem k případné indikaci endodontického ošetření nevýznamný [8].…”
Section: Hodnocení Autotransplantátuunclassified
“…La desinfección química del sistema de conductos radiculares constituye una de las etapas más importantes para lograr el éxito en endodoncia regenerativa. Tradicionalmente, los irrigantes y medicamentos han sido elegidos por su acción antimicrobiana sin tener en cuenta sus efectos sobre las células madre y el micro entorno del conducto 7 En este aspecto, la reducción bacteriana es crucial para lograr la regeneración en los conductos radiculares con ápices inmaduros que presentan una pared dentinaria delgada y frágil. Es por ello, que se indica una mínima instrumentación mecánica de las paredes radiculares.…”
Section: Introductionunclassified